Federated Architecture Based on Knowledge Graphs and Blockchain for Semantic Integration of Public Health Data - Gomes, Nacles B. P.; Salvador, Laís do Nascimento; Silva, Paulo Caetano da (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
The integration of heterogeneous data from the Brazilian Unified Health System (SUS) for epidemiological surveillance remains challenging. Legacy systems such as SIM (mortality) and SINASC (live births) operate independently, without shared identifiers. Existing approaches typically address these dimensions separately, lacking an integrated treatment of semantic mediation, decentralized custody, provenance auditing, and uncertain entity reconciliation over SUS legacy data. This paper presents the Distributed Federated Semantic Architecture (DFSA), combining knowledge graphs, permissioned blockchain, distributed encrypted storage, and fuzzy logic. The solution was validated with real-world data from the municipality of Camaçari, Bahia, Brazil, comprising 5.4 million RDF triples. It achieved a federated latency of less than 10 ms, with an estimated throughput of 1.6 million queries per hour, along with full auditability. The solution also received positive feedback from managers due to the automated generation of indicators.